PENGARUH ENERGI TERMAL DAN MEKANIK TERHADAP TRASNFORMASI LINKOMISIN HIDROKLORIDA I DAN II - Khairunnisa Elfa, Rahmi
Mechanical energy from grinding and thermal energy that exposed to active pharmaceutical ingredients during various pharmaceutical development processes could cause transformation such as polymorphic transformation, desolvation from solvate, hydrate formation, and transformation from crystalline to amorphous form. Thus, transformation of pharmaceutical ingredients could cause physical alterations that would affect the quality of dosage forms. Consequently, it is important to understand the transformation phenomena of active pharmaceutical ingredients that could occur during pharmaceutical development processes. Therefore, this study is conducted to analyze the effect of thermal and mechanical energy on lincomycin hydrochloride form I (hemihydrate) and form II (monohydrate) transformation. Thermal energy is applied by heating the sample at 90 o C for an hour. And the mechanical energy is applied by grinding the sample using mortar grinder for 30 minutes. Characterization was performed using polarization microscope, powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and Karl Fischer titration. PXRD diffractogram of form I remain unchanged on thermal energy exposure even after the form I already has dehydrated. Result analysis of DSC, Karl Fischer titration, and rehydration curve shown that thermal energy could transform lincomycin hydrochloride I into its isomorphic dehydrate form. The isomorphic dehydrate form in the typical room condition immediately stabilize its crystal structure within few minutes by reabsorbing water from atmosphere, while form II did not change or transform by heating at 90 o C. Meanwhile mechanical energy exposure has decreased the intensity of PXRD diffractogram and endothermic peak of DSC thermogram of both polymorph forms. Therefore mechanical energy could transform crystalline form of both polymorphs into its amorphous form and significantly decrease its crystallinity index.